2013
DOI: 10.1111/jopy.12030
|View full text |Cite
|
Sign up to set email alerts
|

Personality Change in the Oldest‐Old: Is It a Matter of Compromised Health and Functioning?

Abstract: The present longitudinal study investigates continuity and change in the personality dimensions of extraversion and neuroticism among the oldest-old. Overall disease load, self-rated health, functional capacity, impaired vision and hearing, self-reported cognitive impairment, and measured cognitive status were tested for their role as potentially relevant late-life predictors of personality change. The sample consists of 408 individuals aged 80-98 in the Swedish OCTO-Twin Study who completed the Eysenck Person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 28 publications
6
57
0
1
Order By: Relevance
“…It supports a prior report of an association between hearing impairment and declines in extraversion (Berg & Johansson, 2014). Using a larger sample of older adults, this study extended these findings by showing that both self-reported hearing and eyesight are independently related to a generalized change across the five traits.…”
Section: Discussionsupporting
confidence: 91%
“…It supports a prior report of an association between hearing impairment and declines in extraversion (Berg & Johansson, 2014). Using a larger sample of older adults, this study extended these findings by showing that both self-reported hearing and eyesight are independently related to a generalized change across the five traits.…”
Section: Discussionsupporting
confidence: 91%
“…Future research might identify life events and social role changes or other sources of change that impact personality development in old age. Changes in health might play key roles in this regard (Berg & Johansson, 2014;Human et al, 2013;Magee, Heaven, & Miller, 2013;Mõttus, Johnson, et al, 2012;Mroczek & Spiro, 2003;Takahashi, Edmonds, Jackson, & Roberts, 2013). Health declines might impact individual personality in similar ways (resulting in mean-level changes), but people differ on when health declines begin to emerge (resulting in rank-order changes).…”
Section: Understanding Personality Development In Old Agementioning
confidence: 99%
“…Franklin et al (2013), demonstrated a strong relationship between extroversion personality, willingness to listen to speech in the presence of background noise, and willingness to wear HAs in older adults. Further, a longitudinal study showed that personality change was linked with HL and social isolation (Berg & Johansson, 2014). Furthermore, studies presented that severity of age-related HL was associated with impaired activities of daily living (Gopinath et al, 2012).…”
mentioning
confidence: 98%